The Discipline of Female Bodiness in TikTok Visual Music - Saputri, Nur Amala (JUSS (Jurnal Sosial Soedirman), 2024)
This article aims to examine the TikTok music phenomenon among generation Z. The author uses a qualitative case study approach using textual analysis and critical paradigms. The object of study described is the music content published by Idgitaf and Mahalini on their official TikTok channel. There are 2 main points as foundings: the construction of a participatory culture carried out through the Duet Challenge feature and new visual music standards through the Filter Challenge promoted by TikTok. This participatory culture normalizes the standards for duets or performing songs today that can be done by professional musicians with fans/ordinary TikTok users (amateur singers). The existence of TikTok's visual features also emphasizes that TikTok's current standardization of digital music forms must emphasize the quality and beauty of its visuals compared to its audio content.